Model of grid resource selection based on the trust moment - Yu-ling LIU; Rui-zhong DU; Jun-feng TIAN; Peng YUAN (Tongxin xuebao)
The trust torque was defined as the product of trust gravitation and trust radius and the grid resource selection model based on trust torque was proposed.The grid resources are divided into many trusted resource domains according to different types and the grid resources of each domain are managed by its domain agent.A resource selection algorithm is realized by trust evaluation of resource nodes and comprehensive judgment of historical transaction experiences,current resource attributes and personal preferences.The algorithm not only pays attention to the service quality of resource selection for users,but also meets the requirements of different users.Simulation results verify the feasibility and effectiveness of our model.